2017
DOI: 10.18632/oncotarget.17388
|View full text |Cite
|
Sign up to set email alerts
|

Trans-scirpusin A showed antitumor effects via autophagy activation and apoptosis induction of colorectal cancer cells

Abstract: Trans-Scirpusin A (TSA) is a resveratrol oligomer found in Borassus flabellifer L. We found that TSA inhibited the growth of colorectal cancer Her2/CT26 cells in vivo in mice. Although some cytotoxic T lymphocytes (CTLs) were induced against the tumor-associated antigen Her2, TSA treatment did not significantly increase the level of Her2-specific CTL response compared to that with vehicle treatment. However, there was a significant increase in the level of TNF-α mRNA in tumor tissue and Her2-specific Ab (antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…For example, in the genetic IL‐10 –/– model of colitis, we showed that resveratrol treatment was able to induce immunosuppressive MDSCs that led to a reduction in clinical parameters in addition to the reduction in CXCR3 expressing T cells . The ability of resveratrol to induce these anti‐inflammatory MDSCs has been shown in our laboratory in other disease models, and been confirmed by others as well . Other studies have shown that the beneficial effects of resveratrol against colitis can be attributed to other mechanisms, such as targeting sphingosine kinase 1 (SphK1) and apoptosis, restoring nitric oxide levels, reducing neutrophil infiltration, inhibiting NF‐κB activation, acting as an antioxidant, as well as inhibiting adhesion molecules .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…For example, in the genetic IL‐10 –/– model of colitis, we showed that resveratrol treatment was able to induce immunosuppressive MDSCs that led to a reduction in clinical parameters in addition to the reduction in CXCR3 expressing T cells . The ability of resveratrol to induce these anti‐inflammatory MDSCs has been shown in our laboratory in other disease models, and been confirmed by others as well . Other studies have shown that the beneficial effects of resveratrol against colitis can be attributed to other mechanisms, such as targeting sphingosine kinase 1 (SphK1) and apoptosis, restoring nitric oxide levels, reducing neutrophil infiltration, inhibiting NF‐κB activation, acting as an antioxidant, as well as inhibiting adhesion molecules .…”
Section: Discussionsupporting
confidence: 60%
“…13 The ability of resveratrol to induce these anti-inflammatory MDSCs has been shown in our laboratory in other disease models, [8][9][10] and been confirmed by others as well. 31,32 Other studies have shown that the beneficial effects of resveratrol against colitis can be attributed to other mechanisms, such as targeting sphingosine kinase 1 (SphK1) and apoptosis, restoring nitric oxide levels, reducing neutrophil infiltration, inhibiting NF-B activation, acting as an antioxidant, as well as inhibiting adhesion molecules. [33][34][35] Resveratrol is also well known to be a ligand for the aryl hydrocarbon receptor (AhR), and our laboratory and others have shown this natural compound's ability to shift T cell differentiation from Th17 to Tregs, which is dependent on this receptor-ligand interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Trans -Scirpusin A (TSA), a resveratrol oligomer, has been reported to inhibit the growth of colorectal cancer in in vivo model. Among different mechanisms involved in its antitumor efficacy, TSA overcomes the tumor-associated immunosuppressive microenvironment by reducing the number of CD25-FoxP3 regulatory T cells and myeloid-derived suppressor cells (73).…”
Section: Dietary Polyphenolsmentioning
confidence: 99%
“…SDS-PAGE and western blotting was conducted as previously described (25). Briefly, cell lysates were evaluated to determine protein levels and then loaded on SDS-PAGE gel.…”
Section: Methodsmentioning
confidence: 99%